Pelvic inflamatory disease and sterility - Carvalho, Newton S.; Guimarães, Ana Cecília P.; Breckenfeld, Débora C.; Bigolin , Silvane (Brazilian Journal of Sexually Transmitted Diseases, 1999)
The relation between pelvic inflamatory disease (PID) and sterility has been a topic of frequent discussions and publications. lt is observed on its pa-thogenesis that among the agents which can cause PID Chlamydia trachomatis is the most common in our neighbourhood. Many autors have described the tubal and peri-tubal changes which can be developed in pelvic inflamatory disease, resulting in infertility. Most of the cases have diverse sintoms, making di-fficult to diagnosis and distinguish from other geni-tal pathologies. Prevention of pelvic inflamatory dise-ase and of its sequelaes depends on effective control of trasmission.